ANALISIS PROGRAM PEMBERDAYAAN ORGANISASI PENGELOLA ZAKAT DI KABUPATEN KOTAWARINGIN TIMUR DAN KOTAWARINGIN BARAT - Zulkifli Zulkifli; Muhammad Noor Sayuti; Wahyu Akbar; Hasnita Hasnita; Anisa Anisa (IAIN Batusangkar, 2023)
The purpose of this study was to analyze, study, and find out the obstacles to various empowerment programs for zakat management organizations in empowering communities in East Kotawaringin and West Kotawaringin Regencies, Central Kalimantan Province. This type of research is field research with the research subjects being BAZNAS Kotawaringin Timur, LAZ Nurul Fikri Sampit Branch, BAZNAS Kotawaringin Barat and LAZNAS Yakesma Pangkalan Bun Branch. Data in this study were collected by interviews, observation and documentation. Meanwhile, data analysis was carried out deductively to obtain an overview of events in the field and then conclusions related to the research were obtained. The results of this study indicate that the empowerment program for zakat collection organizations in Kotawaringin Timur and Kotawaringin Barat districts in empowering communities through zakat needs to pay attention to the form and mechanism of the program, mustahik's response, and continuous assistance, developing long-term productive businesses, providing productive business training, and opening job opportunities for mustahik through cooperation with the government and the private sector. Obstacles faced by these institutions include a lack of human resources, good faith from recipients of funds, and community literacy. Therefore, efforts are needed to change the mindset and increase community literacy as well as establish cooperation with related agencies to increase the effectiveness of the empowerment program.